Should early health investments work? Evidence from an RCT of a home visiting programme - Deirdre Coy; Orla Doyle (University College Dublin, UCD Centre for Economic Research, 2020)
Evidence for the short-term impact of early intervention on childhood health is weak and inconsistent. Using rigorous methods, careful hypothesis setting, and socioeconomic contextualisation, we examine the impact of an Irish home visiting programme on child health. The treatment provides mentoring visits from pregnancy until school entry to improve child outcomes through positively affecting parenting. In a context where socioeconomic inequalities in health have yet to emerge, modest effects by age four are found, driven by reduced hospital attendance. Conflicting reports in the literature may thus arise from an overexpectation of hypothesized effects and failure to account for social contexts.
Keywords: I14; I12; J13; 330; Home visiting programme; randomised controlled trial; child health; health inequality; human capital formation